Meningkatkan Keterampilan Menulis Karangan Narasi Siswa SD Melalui Think-Talk-Write Berbantu Media Gambar - Amaliah, Amaliah; Bahri, Aliem; Rahayu, Sri (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aims to determine the planning, implementation, and improvement of learning outcomes for narrative essay writing skills in class V UPT SPF SDN Kalukuang IV students, Makassar City. This type of research is class action research (Class Action Research) which consists of two cycles where each cycle is carried out in four meetings. The focus of this research is 1) Narrative essay writing skills and 2) Use of think talk write strategies assisted by image media in class V UPT SPF SDN Kalukuang IV Makassar City. Research procedures include planning, implementing actions, observing and reflecting. The research subjects were 32 class V students, with details of 15 boys and 17 girls. The collected data was analyzed using quantitative and qualitative analysis. The results of this research are: (1) In the first cycle, the average value of learning outcomes for class V UPT SPF SDN Kalukuang IV Makassar City students was obtained, namely 59.2 (2) In the second cycle, the average value of learning outcomes for class V UPT SPF students was obtained. SDN Kalukuang IV Makassar City was higher, reaching 90. The learning completion of class V UPT SPF students at SDN Kalukuang IV Makassar City also increased. In cycle I, 10 (31%) students achieved learning completeness, while in cycle II 30 (94%) students achieved learning completeness and classical learning completion was achieved. This means that learning completeness in cycle II was achieved classically because the number of students who completed it was more than 80%. Based on the results of the research above, it can be concluded that the skill of writing narrative essays for class V UPT SPF SDN Kalukuang IV Makassar City through the application of the think talk write strategy assisted by image media has increased.